English English - Hernugroho, Ananto; Amal, Ahmad Ikhlasul; Melastuti, Erna; Hendrawan, Gagah Satria (Jurnal Surya, 2025)
Introduction: Tuberculosis (TB) is one of the 10 leading causes of death in the world. TB treatment that requires regularity over a long period of time has an impact on decreasing motivation for treatment in TB patients, this decrease in motivation can cause boredom which results in incomplete TB treatment. One of the external factors that can increase motivation for treatment is support from health personnel and family. This study aims to determine relationship between support from health personnel and family with treatment’s motivation in Pulmonary TB patients. Methods: This quantitative study uses a correlation analysis design with a cross-sectional approach. The sample in this study was 70 Pulmonary TB patients who were taken using the total sampling technique. Data collection was carried out using a valid and reliable questionnaire to measuring health personnel’s support and family also treatment’s motivation. Data analysis was carried out using the Spearman Rank test. Results: A total of 44 patients (62.9%) felt good support from health personnel, 51 patients (72.9%) felt good family support, and 44 patients (62.9%) had high treatment’s motivation. There was a significant relationship between health personnel’s support (p = 0.001; r = 0.344) and family’s support (p = 0.0001; r = 0.497) with treatment’s motivation. Conclusion: There is a significant relationship between health personnel’s support and family with treatment’s motivation for pulmonary TB patients. Health personnels can visit families' homes to provide support to increase patient motivation. Keywords: Family, Health Personnel, Motivation, Support, Tuberculosis